Rancang Bangun Aplikasi Menu Makanan Berbasis Android pada Warung Nasi Goreng Pohon Asem - Azfari Ikhsan; Munawaroh (Journal of Research and Publication Innovation, 2024)
Humans generally want everything to be easily done, as well as sellers who want to take advantage of Smartphone technology to carry out their work more easily, such as recording orders requested by customers. At the Nasi Goreng Pohon Asem stall, there are shortcomings such as unrecorded orders and the occurrence of forgotten orders by buyers. Subscribed shoppers even use other apps to order remotely. Therefore, an application is needed to help sellers manage orders, as well as buyers in ordering food. Flutter, a framework known for its good performance and ease of implementation, can be used to develop mobile applications for this purpose. The development of food menu applications using Flutter with the Rapid Application Development (RAD) method is very important to increase the effectiveness and efficiency of order management at the Nasi Goreng Pohon Asem stall. The result of this study is that the application can help sellers in managing food orders, and also help buyers in ordering without using the Whatsapp application or going to a stall.